Efficient Signal Quality Monitoring of GNSS Signals Disturbed by Evil Waveforms - Fernando D. Nunes; Fernando M. G. Sousa (Navigation)
Evil waveforms (EWFs) are anomalies in signals transmitted by a global navigation satellite system, provoked by electric malfunctions, that can significantly degrade the accuracy of the receiver’s position, velocity, and time solution. In this work, cross-correlation functions of a received signal disturbed by EWF distortion and the locally generated code signal are derived for threat models TM-A, TM-B, and TM-C, with expressions obtained for binary phase shift keying, binary offset carrier (BOC), and composite BOC pilot modulations. Closed-form expressions are offered in terms of sine integral functions for TM-A. A description is presented on how to use these results to assess the performance of EWF detectors through semi-analytic simulation, allowing the detectability and hazard regions to be determined in a computationally efficient way.